Vertigo and Presyncope: Clinical Presentation of Sinus Dysfunction - (:unkn) unknown (My University, 2021)
Aim: Aim of this case presentation is to emphasize on the ECG recording of patients with history of drowsiness or presyncope.Case: 87-year-old male was admitted to the emergency department (ED) with complaints of dizziness, lightheadedness, and drowsiness. He had a history of coronary artery disease and he was being treated as per vertebrobasilar insufficiency because of symptoms. Atrioventricular nodal reentrant tachycardia (AVNRT) and right bundle branch block with bifascicular block was documented in the electrocardiography (ECG) records obtained in our ED. Following the treatment with diltiazem infusion, sinoatrial arrest-pause was captured during the monitorization in the ED. He was handed over to cardiology department for electrophysiologic (EP) study afterwards.Discussion: Sinoatrial (SA) node dysfunction results from any pathology in impulse generation by pacemaker cells in the node or in conduction perinodal transmission cells. The etiologic factors leading to sinus node dysfunction are classified into two pathologies; first is the intrinsic pathology of the SA node, and second group is external causes that affect SA node. The most common intrinsic cause is the agerelatedfibrosis of the natural pacemaker cardiac tissue in the SA node. If the pause is longer than 3 seconds, thepatient is a candidate for ablation therapy which depends on the result of the non-fluoroscopic electroanatomic mapping (CARTO) ablation technique.Conclusion: Neurological symptoms such as drowsiness and presyncope may often manifest as a result of underlying cardiac pathology. ECG is a very useful tool for these patients if the records are taken at appropriate time.

Amaç: Bu vaka sunumunun amacı, öyküsünde baş dönmesi veya presenkop olan hastalarda EKG kaydının önemine vurgu yapmaktır. Olgu: 87 yaşında erkek hasta acil servise bayılma hissi, sersemlik ve baş dönmesi şikayetleriyle başvurdu. Hastada koroner arter hastalığı öyküsü vardı ve semptomları nedeniyle vertebrobaziler yetmezlik tedavisi almakta idi. Elektrokardiyografi (EKG) kayıtlarında acil servisimizde atriyoventriküler nodal reentran taşikardi ve bifasiküler blok ile birlikte sağ dal bloğu tespit edildi. Acil serviste diltiazem ile tedavi edilirken sinoatriyal pause gelişti. Daha sonra elektrofizyolojik çalışma ve yakın izlem için kardiyoloji bölümüne devredildi. Tartışma: Sinoatriyal (SA) düğümde disfonksiyon, düğümdeki impuls üreten pacemaker hücrelerde veya perinodal iletide görevli hücrelerdeki patoloji sonucunda ortaya çıkar. Sinus düğümü disfonksiyonuna yola açan etyolojik faktörler iki gruba ayrılır. İlki SA düğümün intrinsik patolojisi, ikinci grup SA düğümü etkileyen ekstrinsik patolojilerdir. En sık intrinsik neden yaşa bağlı olarak SA düğümdeki doğal pacemaker kardiyak dokuda gelişen fibrozisdir. Eğer sinus pause 3 saniyeden uzun sürüyor ise hasta floroskopi kullanmadan uygulanan elektroanatomik haritalama sistemi (CARTO) ablasyon tekniği sonucuna bağlı olarak ablasyon tedavisine adaydır. Sonuç: Hastalarda baş dönmesi, presenkop gibi nörolojik semptomlar altta yatan kardiyak patoloji sonucunda ortaya çıkabilir. Eğer kayıtlar uygun zamanda alınırsa EKG bu hastalar için çok faydalı bir araçtır.
Vertigo ve Presenkop : Sinüs Disfonksiyonunun Klinik Görünümü